Modelling of elastoviscoplastic properties of the subgrade. Problem statement 2 - V. M. Bel’Kov (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
Research of railway embankments in terms of physical and chemical mechanics were conducted discretely, without the creation of a coherent model of stability of layered systems, taking into account all the determining factors. The article shows that attention should be focused on the process of blurring the boundaries "crushed stone granules - layer of sand", "layer of sand - loam or clay" when running freight trains as well as the limiting stability of layered granular system. The presence of natural inhomogeneities of structure and change in the density of the underlying soils, especially in wet periods, violations of construction technology of sugrade embankment, dynamic loads on the rails due to vibrations of "bogie - train" system leads to the formation of wave-like ground subsidence. Vibration fields generated in the water and viscoplastic fluids, increase the rate of rise of water in capillaries and porous media in dozens of times because of reduced hysteresis in the contact angle of wet and wall effects. Therefore, the vibration of the field arising from the train handling, contribute to flooding and penetration of clay soils in the pore space of sand due to a significant reduction of the structural viscosity and yield value of a non-Newtonian media. In studies of clay media and other systems all the effects should be taken into account: deformation thixotropy, "gelation" in strong electromagnetic fields, wall effects, which significantly increase the flow rate of hydrated clay in suffosion capillaries of sand and crushed stone cushion layer.